V. Study of the Experimental Oligoganglionosis of the Colon - Ando, H. (Nippon Daicho Komonbyo Gakkai Zasshi, 1978)
For the investigation of pathophysiology in the oligoganglionosis of colon, the experimental destruction of Auerbach's plexus by temporary hypoxia was induced in dogs. Compared the EMG of the oligoganglionic segments with normal EMG which was classified into five basic patterns by ourselves, the frequent appearance of spike bursts was characteristic, suggesting the role of Auerbach's plexus as inhibitor against the electric activity of the colon. This spike burst was inhibited by β stimulator and accelerated by β blocking agent. By X-Ray examination, this oligoganglionic segment has shown no narrowing as like as Hirschsprung's disease but some degree of disturbed bowel movement.